A CARBON ISOTOPE REFERENCE SCALE FOR THE LOWER CAMBRIAN SUCCESSION IN SIBERIA: REPORT OF IGCP PROJECT 303 - Brasier M.D.; Corfield R.M.; Rozanov A.Y.; Zhuravlev A.Y.; Derry L.A. (My University, 1994)
Four sections from the mid-Atdabanian to lowest Toyonian (middle Cambrian) along the Lena River of Siberia were sampled for carbon isotope stratigraphy. These show a mainly heavy but highly oscillatory δ13C signature for the Atdabanian to mid-Botomian interval, coincident with the major phase of invertebrate innovation. A prolonged interval of negative δ13C followed until late Toyonian times, coincident with Botomian-Toyonian mass extinctions. Eleven carbon isotope cycles are identified through the lower Cambrian, which should now be tested for their utility in global correlation and relationship to bioevents in the Cambrian explosion.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская